Strategi Pengembangan Komoditas Unggulan Sektor Pangan Pada Kawasan Agropolitan Di Kota Pagar Alam - Zenal Mutaqin; Hala Haidir (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Pagar Alam City is one of the areas located in South Sumatra Province, coinciding at the foot of the mountains, so it has superior commodities in the form of coffee and tea producers. In addition, there are other commodities consisting of cultivating vegetables and fruits. This commodity is a source of livelihood for the majority of the population as farmers. Along with the variety of natural products available, it is felt that they have not fully developed optimally, especially vegetables, fruits and of course human resources (HR). In addition, there are still lands that have not been utilized optimally as agropolitan areas. This study aims to develop a strategy for agricultural and plantation commodities and to take advantage of food potentials, existing infrastructure and facilities. The methods used are analytical hierarchy process (AHP) and SWOT analysis. The results showed that the first priority results from fruits, vegetables and plantations 1) Strategies to take advantage of strengths and opportunities, namely improving small and medium enterprises, developing technology, infrastructure, human resources. 2) Strategies to take advantage of weaknesses and opportunities, namely providing venture capital / subsidies to farmers and cooperation between parties. 3) Strategies to take advantage of strengths in facing challenges, namely household product management, institutional formation in the form of cooperatives for business progress, 4) strategies to take advantage of weaknesses and challenges, namely socialization between stakeholders for human resource advancement in order to form creativity and marketing innovation in anticipation of business competition. Keywords: Superior commodities, Agropolitan, Strategy, AHP, SWOT